2020
DOI: 10.1021/acs.langmuir.0c00135
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation Kinetics of Magnetic Nanoparticle Clusters: Iron Oxide Nanospheres vs Nanorods

Abstract: A detailed study of the sedimentation kinetics of iron oxide nanoparticle (IONP) clusters composed of nanospheres and nanorods is presented. Measurements were performed to determine the absorbance of an IONP suspension undergoing sedimentation over time by using a UV–vis spectrophotometer with simultaneous monitoring of the hydrodynamic diameter of the clusters formed with dynamic light scattering (DLS). Mathematical analysis based on Happel’s spherical and cylindrical models was conducted to reveal the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
(92 reference statements)
2
24
0
Order By: Relevance
“…Additionally, the trivial effect of gravitational sedimentation on magnetophoresis has also been demonstrated in our experiments using a TODA magnetic nanorod (with a diameter of ∼20 nm and a length of ∼300 nm). 56,84 In the presence of a low-gradient magnetic field generated by a hand-held cylindrical magnet, the removal of a magnetic nanorod can be accomplished within 3 min. 56 On the other hand, under the action of only gravitational force (in the absence of a magnetic field), complete settling out of a magnetic nanorod is still not yet achieved after 100 min of gravitational sedimentation.…”
Section: ■ Fundamental Conceptsmentioning
confidence: 99%
“…Additionally, the trivial effect of gravitational sedimentation on magnetophoresis has also been demonstrated in our experiments using a TODA magnetic nanorod (with a diameter of ∼20 nm and a length of ∼300 nm). 56,84 In the presence of a low-gradient magnetic field generated by a hand-held cylindrical magnet, the removal of a magnetic nanorod can be accomplished within 3 min. 56 On the other hand, under the action of only gravitational force (in the absence of a magnetic field), complete settling out of a magnetic nanorod is still not yet achieved after 100 min of gravitational sedimentation.…”
Section: ■ Fundamental Conceptsmentioning
confidence: 99%
“…It has been shown that magnetic nanoparticles and magnetic fields may induce destructive heat against the targeted cells, inducing apoptosis and cell death. , Besides, magnetic nanoparticles can internalize inside the targeted cells, allowing the combined therapeutic agents to precisely exert the need for intercellular activity . It is also highly possible that the magnetic force can direct the particles to biofilms’ core, resulting in severe physical damage to the bacterial colonies. , For that, we examined the effect of the microemulsion containing the SPIONs without the photosensitizer under the magnetic field force (Figure B). We found that using microemulsions containing only SPIONs under the magnetic field resulted in around 1-log reduction, which is considered a minor reduction when evaluating the antibacterial properties of dental products.…”
Section: Resultsmentioning
confidence: 99%
“…58 It is also highly possible that the magnetic force can direct the particles to biofilms' core, resulting in severe physical damage to the bacterial colonies. 17,59 For that, we examined the effect of the microemulsion containing the SPIONs without the photosensitizer under the magnetic field force (Figure 5B). We found that using microemulsions containing only SPIONs under the magnetic field resulted in around 1-log reduction, which is considered a minor reduction when evaluating the antibacterial properties of dental products.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, microbead‐based assays have several advantages, such as no washing steps compare to conventional flat microarray, multiplexed assay using an encoded microbead, amplified signal and short assay time because of the freely moveable microbeads in mediums [101,102]. Due to these considerations, various other techniques have been employed to form magnetically responsive bead of all types by using nanoparticles as the main building blocks [32,103,104].…”
Section: Design Criteria Of Magnetophoretic Systemmentioning
confidence: 99%
“…employed to form magnetically responsive bead of all types by using nanoparticles as the main building blocks [32,103,104].…”
Section: Particle Designmentioning
confidence: 99%